MATHEMATICAL MODEL OF THE GENERATION OF IRON-MANGANESE NODULES IN THE BLACK SEA - Belyayev V.I.; Konduforova N.V. (My University, 1987)
According to the model previously derived, nodules in the surface layer of sediment are formed by deposition, dehydration and crystallization of colloidal iron and manganese hydroxide on various nuclei resting on the surface of the sediments. The authors tested The authors tested the principal hypothesis on which the model is based. Experimental results show that the zones with elevated concentrations of manganese compounds were found in the same regions where nodules are found, i.e., in the vicinity of Kalamit Bay and off the Bulgarian coast near Cape Kaliakra. This result shows that one can simulate nodule generation in terms of the concentration fields of the materials involved in such generation.